Reimagining the Linguistic Roadmap as a Key Variable of a Multidisciplinary Approach - Siregar, Iskandarsyah (Britain International for Academic Research (BIAR) Publisher, 2025)
This article critically explores the underrecognized role of linguistics in multidisciplinary research and problem-solving. In response to global challenges that are increasingly communicative, symbolic, and culturally complex—such as misinformation, climate discourse, public health crises, and digital ethics—the study argues for a reimagined “linguistic roadmap” as a central variable in cross-disciplinary inquiry. Rather than viewing language merely as a communication tool, the paper reframes linguistics as an epistemological and methodological contributor to knowledge production and societal transformation. The research employs a qualitative, exploratory-descriptive design supported by critical discourse analysis and theoretical modeling. Drawing from scholarly literature, institutional frameworks, and case studies, the study identifies patterns in which linguistic expertise is either excluded or only superficially included in multidisciplinary collaborations. The findings reveal five core functions for a redefined linguistic roadmap: discursive mapping, cognitive framing diagnostics, cultural-pragmatic interfacing, ethical reflexivity, and applied linguistic integration (e.g., NLP and corpus analysis). Three case studies—in climate change communication, intercultural medical pragmatics, and legal technology—demonstrate the practical impact of linguistics when applied at the conceptual design level. These cases show that linguistic integration enhances both ethical coherence and operational efficacy in cross-sector initiatives. The article concludes that the minimal presence of linguistics in interdisciplinary research stems from epistemological hierarchies and public misconceptions. It advocates for structural reform across research institutions, funding mechanisms, academic curricula, and linguistics departments to reposition the field as a foundational science of meaning, cognition, and interaction. Ultimately, reimagining the linguistic roadmap is not only necessary for advancing interdisciplinary research but essential for building inclusive, context-sensitive, and ethically grounded solutions to today’s most pressing global problems.